Spontaneous intracranial hypotension: the role of radiology in diagnosis and management. Issue 3 (March 2022) - Carlton Jones, L.; Butteriss, D.; Scoffings, D.
Abstract : Spontaneous intracranial hypotension (SIH) is a condition that results from leakage of cerebrospinal fluid (CSF) from the spine, and which typically presents with debilitating orthostatic headache, but can be associated with a wide range of other symptoms. The causes of spontaneous CSF leaks that lead to SIH include dural tears, leaking meningeal diverticula, and CSF–venous fistulas. Imaging plays a central role in the initial diagnosis of SIH and in its subsequent investigation and management. This article reviews the typical neuroimaging manifestations of SIH and discusses the utility of different myelographic techniques for localising spinal CSF leaks as well as the role of image-guided treatment.